Reflection of the world of plants in the system of the Belarusian and Slovak verbs - Raago, Pavel A. (Journal of the Belarusian State University. Philology, 2019)
The paper proposes semantic-syntactical classification of the verbs with the subject seme ‘plant’ and attempts to show, what kind of information about the world of plants is contained in the verbs of the Belarusian and Slovak languages. This information is very diverse, which allows us to analyze it at three levels: understanding of the functional role of the plant; reflection of ontological properties and characteristics of plants within the bounds of particular semantic classes; denotation. The comparative analysis makes it possible to determine distinctive features of the reflection of the world of plants in the verbal semantic of the Belarusian and Slovak languages.